Identifikasi dan Pengendalian Bahaya K3 Pada Aktivitas Suplai Air Bersih untuk Kapal di Dermaga XYZ Menggunakan Metode JSA dan HIRARC - Yanita Vidya Pramesthi; Tranggono (Jurnal Serambi Engineering, 2025)
The water supply activity at XYZ Dock is a high-risk work area. The purpose of this research is to identify hazard risks and provide suggestions for controlling occupational safety and health (OSH) hazards at XYZ Pier. The methods used in this research are Job Safety Analysis Hazard Identification (JSA) and Hazard Risk Assessment and Control (HIRARC). Based on the results obtained from the identification of hazards in each water supply activity, the data obtained in the hose laying activity has 4 medium hazards and 2 low hazards. In the clean water distribution activity, there is 1 high risk, 2 medium risks and 1 low risk. In the activity of releasing the hose there is 1 risk of medium value and 3 risks of low value. After risk control, there is 1 medium risk and 5 low risks in the hose laying activity. In the clean water distribution activity there is 1 medium value risk and 3 low value risks. In the hose removal activity, there is 1 risk of medium value and 3 risks of low value. Therefore, this investigation is able to reduce the risk of potential hazards in the clean water supply activities at XYZ pier.